Active and Healthy Aging : the Role of Public, Private and Voluntary Sectors in Providing Outdoor Recreation for Older Adults - Kling, Kristin Godtman; Zingmark, Magnus ; 0000-0002-1087-8656 (Journal of Population Ageing, 2025)
Access to outdoor leisure activities is central to supporting active and healthy ageing. To address the lack of research on services supporting continued engagement, this study examines how public, voluntary and private sectors provide outdoor recreation services for older adults. This study uses a qualitative research design to draw on interviews, a workshop, and field observations conducted in a Swedish municipality. Grounded in the capability approach and theories of active ageing, the study contributes to a better understanding of how opportunities for participation in outdoor recreation are shaped by service provision and structural conditions. This study identifies positive examples of outdoor recreation services but also gaps, characterised by the level of challenge in the activities that stakeholders in different sectors provide. Whereas activities provided by public senior centres were conducted in accessible terrain and inclusive for people with functional limitations, opportunities for slightly more challenging activities were lacking. Activities provided by voluntary organisations offered opportunities for more challenge, with the risk of exclusion for those with mobility limitations. The private sector, despite interest, did not actively provide outdoor recreation for older adults due to demand uncertainties. A structural barrier across all sectors was limited access to transport. This study contributes to the literature by identifying the need for tiered outdoor recreation programs, improved transport solutions, and cross-sector collaboration. While situated in a Swedish context, the findings offer conceptual and practical relevance for broader efforts to provide diversity in outdoor recreation services that support active ageing for different groups. A more coordinated, inclusive approach through policy and resource allocation across sectors is essential to support outdoor engagement in ageing populations.
.
Keywords: AcTive ageing; Collaboration; Nature experience; Public health; Sweden